CARA BELAJAR DAN MOTIVASI BELAJAR PENGARUHNYA TERHADAP HASIL BELAJAR SISWA PADA MATA DIKLAT AKUNTANSI - Linawati, (Pendidikan Ekonomi, 2010)
The study is intended to investigate the influence of eleventh graders learning ways and motivation on the learning results in accounting class at SMKN 1 Mojoagung Jombang. The subjects were 111 students in eleventh grade of accounting major at SMKN 1 Mojoagung. The data were collected with questionnaires and documents of accounting scores. The data were then analyzed with stepwise multiple regression. The results of the study revealed that the learning ways and motivation simultaneously affect significantly the learning results.